2013
DOI: 10.1007/s10585-013-9565-x
|View full text |Cite
|
Sign up to set email alerts
|

Leading malignant cells initiate collective epithelial cell invasion in a three-dimensional heterotypic tumor spheroid model

Abstract: Solid tumors consist of genetically and phenotypically diverse subpopulations of cancer cells with unique capacities for growth, differentiation, and invasion. While the molecular and microenvironmental bases for heterogeneity are increasingly appreciated, the outcomes of such intratumor heterogeneity, particularly in the context of tumor invasion and metastasis, remain poorly understood. To study heterotypic cell-cell interactions and elucidate the biological consequences of intratumor heterogeneity, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
158
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 78 publications
9
158
1
Order By: Relevance
“…Multiple studies demonstrate that intrinsic differences in invasive motility between tumor cells affect the leader follower arrangement of collectively invading cancer cells [111,112]. For example, MT1-MMP expressing breast cancer cells generate micro-tracks that enable migration of trailing cancer cells, and collective invasion is abolished when MT1-MMP-mediated proteolysis is disrupted [112].…”
Section: Mechanisms Of Breast Tumor Invasion and Their Cell Interactionsmentioning
confidence: 99%
“…Multiple studies demonstrate that intrinsic differences in invasive motility between tumor cells affect the leader follower arrangement of collectively invading cancer cells [111,112]. For example, MT1-MMP expressing breast cancer cells generate micro-tracks that enable migration of trailing cancer cells, and collective invasion is abolished when MT1-MMP-mediated proteolysis is disrupted [112].…”
Section: Mechanisms Of Breast Tumor Invasion and Their Cell Interactionsmentioning
confidence: 99%
“…It has been shown that mechanical cues, such as substrate stiffness or local stresses, have bearing on cellular behavior in many contexts [1][2][3][4][5][6]. For example, it has been shown that extracellular matrix (ECM) stiffness can promote the onset and progression of cancer [7][8][9][10], and that metastatic cancer cells exert greater traction forces than their healthy counterparts [11].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for that is mainly because precise quantification of reorganized collagen tissue in vivo is significantly restricted by existing methods. Therefore, in vitro 3D models have been constructed to build linear oriented matrices in microchannels by mechanical strain and have demonstrated that 3D matrix alignment facilitates persistent migration of tumor cells (9,(19)(20)(21)(22). For example, Jimenez Valencia et al studied cell behaviors in and around spheroids, which could be regarded as a tumor model at an early stage of the intravasation process.…”
mentioning
confidence: 99%